THE ANALYSIS OF THE OUTPATIENT PHARMACY INSTALLATION SERVICES SYSTEM IN HOSPITAL USING ARENA SIMULATION METHOD (Case Study in ABC Hospital) - Radityo Dimas Mudjiono; Mukhlis; Joko Purnomo; Rofi Hidayaturrahman (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2024)
ABC Hospital is a type A hospital. ABC Hospital is one of the referral centers for both TNI agencies in the eastern region and regional hospitals in Surabaya and its surroundings. For this reason, the services provided must be able to provide a level of satisfaction to the patients who seek treatment. To support this implementation, it must be supported by all parts related to the patient service process. One important part that supports the running of a good service process is the pharmaceutical installation, especially the outpatient pharmacy installation. Where the entire service process in the hospital will end at the pharmacy installation. Outpatient pharmacy installations are special because this process is carried out by the patient or their family, which is different from inpatient treatment where drugs or processes in the pharmacy installation are usually carried out by the nurse on duty in the inpatient room. The author uses arena simulation to analyze and obtain results both for existing conditions and results from experimental scenarios. Where the process begins by determining the distribution model from data observed in the field using analyzer input and then carrying out simulations, validation tests, and verification tests. Then carry out several experimental scenarios using the process analyzer. From the experimental results, we obtained better results than the existing conditions in the non-mixed (+1) and packaging (+1) scenarios, resulting in an improvement in the response variable of 15.2%.